MODL-10. Tumor-brain-organoids as a model for pediatric brain tumors research. (3rd June 2022) - Riedel, Nicole; De Faria, Flavia W; Walter, Carolin; Bruder, Jan M; Kerl, Kornelius
Abstract: BACKGROUND: Embryonal brain neoplasms like atypical teratoid rhabdoid tumor (ATRT) or embryonal tumor with multilayered rosettes (ETMR) still have a very poor outcome despite intensive treatment including chemotherapy, irradiation and surgery. To date, precision oncology has identified clinically relevant innovative therapeutic targets only for a minor subpopulation of pediatric brain tumor patients, which may be due to current in vitro screens not recapitulating the cellular heterogeneity and cellular interactions in vivo. As cellular heterogeneity and cellular interactions majorly influence the response of tumor cells to treatment, we established an innovative 3D screening platform that combines human neural tissue surrounding primary tumor tissue. METHODS: We established a model of tumor-brain-organoids (TBO) by incorporating embryonal tumor cells (ATRT and ETMR tumor cells) into hiPSC-derived forebrain organoids. Using whole mount immunostaining (WMI), we evaluated cancer-phenotype, the neuronal and progenitor cell distribution in brain organoids, and we performed drug screening analysis. Furthermore, we used single-cell RNA-sequencing to characterize the cellular heterogeneity and the effect of tumor-organoid cell-cell communication on transcriptional programs. RESULTS: ATRT as well as ETMR tumor cells incorporated extensively into the organoid tissue. We observed remarkable differences in the invasiveness of ATRT-MYC cells into TBO in comparison with ATRT-SHH and ETMR cells via high content imaging. Moreover, tumor cells affected the gene expression of different cell types of the organoid by upregulating genes of important signaling/growth related pathways (e. g. MAP2K2, IGFBP2) and epigenetic regulators (like BRD7). Screening through a 300 compound FDA-approved drug library in these TBO, we identified potential innovative therapeutic approaches against these embryonal tumors. CONCLUSION: Tumor-brain-organoids can be used as a platform to study tumor biology, tumor interactions with its neural tissue microenvironment, as well as for high-throughput drug and toxicity screening in pediatric brain tumor precision oncology.